2021
DOI: 10.3390/ijms222212328
|View full text |Cite
|
Sign up to set email alerts
|

Garlic Volatile Diallyl Disulfide Induced Cucumber Resistance to Downy Mildew

Abstract: Allicin compositions in garlic are used widely as fungicides in modern agriculture, in which diallyl disulfide (DADS) is a major compound. Downy mildew, caused by Pseudoperonospora cubensis (P. cubensis), is one of the most destructive diseases and causes severe yield losses in cucumbers. To explore the potential mechanism of DADS-induced cucumber resistance to downy mildew, cucumber seedlings were treated with DADS and then inoculated with P. cubensis at a 10-day interval. Symptom observation showed that DADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…It is difficult for the pathogens to obtain allicin resistance and as a consequence, allicin has been used to control gray mold in table grape and strawberry ( 7 , 8 ). In addition, allicin can affect cell division and promote root growth in tomato ( 9 ). Perillaldehyde (PA) is a natural monoterpenoid compound extracted from Perilla frutescens , which has been historically used as a popular leafy vegetable.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult for the pathogens to obtain allicin resistance and as a consequence, allicin has been used to control gray mold in table grape and strawberry ( 7 , 8 ). In addition, allicin can affect cell division and promote root growth in tomato ( 9 ). Perillaldehyde (PA) is a natural monoterpenoid compound extracted from Perilla frutescens , which has been historically used as a popular leafy vegetable.…”
Section: Introductionmentioning
confidence: 99%
“…It is an effective approach to resist pathogens using endogenous and exogenous plant activators such as salicylic acid (SA), jasmonic acid (JA), abscisic acid, BTH, DFL, diallyl disulfide, and so on. These plant activators act on the host by activating immunologic mechanisms to prevent the pathogen invasion, which involve plant hormone signal transduction, phenylpropanoid biosynthesis, and MAPK signaling pathway 43–45 . In this work, the top two KEGG pathways of DEGs were enriched on plant hormone signal transduction and phenylpropanoid biosynthesis.…”
Section: Resultsmentioning
confidence: 89%
“…These plant activators act on the host by activating immunologic mechanisms to prevent the pathogen invasion, which involve plant hormone signal transduction, phenylpropanoid biosynthesis, and MAPK signaling pathway. [43][44][45] In this work, the top two KEGG pathways of DEGs were enriched on plant hormone signal transduction and phenylpropanoid biosynthesis. There are two up-regulated JA responsive genes (JAZ and MYC2), three ethylene (ET)-responsive genes (ETR, CTR1, and EBF1/2), and one SA-responsive gene (TGA) in plant hormone signal transduction.…”
Section: Degs and Deps Involved In Immunitymentioning
confidence: 99%
“…Previous transcriptome analysis has revealed that starch and sucrose metabolism and plant hormone signal transduction may play important roles in the resistance mechanism of plants [ 49 , 50 ]. In this study, 17 DEGs were significantly enriched in the plant hormone signal transduction pathway.…”
Section: Discussionmentioning
confidence: 99%